SCHOOL ECONOMY IN THE INVENTING EDUCATION PARADIGM - Anatoliy Alexandrovich Lepeshev (Science and Innovation Center Publishing House, 2018)
Requirements applied to specialists for working in the sixth wave of innovation, i.e. Industry 4.0, determines the necessity of education system improvement concerning training solution and, as a result, creation of inventive ideas. Today in our country this process is stimulated by various competitions, including financing for the implementation of results. In training programs knowledge approach still prevails. The corresponding methods, along with stimulation, are included into educational programs in leading foreign educational institutions, mostly at universities. If in previous decades mostly divergent methods were studied (morphological analysis, the focal objects method, synectics, etc.), then now the leading place is taken by theory of inventive problem solving – TRIZ created in the former USSR by G.S. Altshuller in connection with the increasing leading corporations requirement for specialists in TRIZ. This fact gives Russia essential competitive advantages in the innovative way of development. For effective use of this advantage it is important to form the TRIZ-based innovative thinking beginning from school days. For this purpose authors developed new methods in TRIZ-pedagogics, uniting metasubject results (in higher education institutions – competences) into the system of innovative thinking. As a result, both educational and economic effects are achieved: the intellectual property created in educational process. For schools it is the possibility of significant improvement of financing causing importance of new mechanisms of intellectual property fixation, protection and implementation. Recommendations about creation of such system are provided in the article.